Light Synergy: Solar Cell Output Optimization through Light Convergence Method (Integration of Convex Lens and Light Reflection) - Ahmad Eko Suryanto; Sukardi Sukardi; Agung Samudra; Pri Ariadi Cahya Dinata (Universitas Sultan Ageng Tirtayasa, 2025)
This study experimentally examines how integrating a convex (Fresnel) lens and a reflector affects solar cell output performance, analyzing impacts of variations in lens distance, illuminance, and associated temperature changes. Experimental methodology involved testing various lens-to-cell distance configurations under both natural sunlight and artificial lighting. Results under direct sunlight demonstrate significant enhancement: a Fresnel lens positioned at an optimal 10 cm distance achieved a peak power output of 0.939 W, a 199.04% increase compared to baseline power (0.314 W) measured without optical components. Reflector use proved beneficial by redirecting unabsorbed light onto the solar cell's active surface and promoting more uniform distribution of concentrated light. This potentially reduces severe localized temperature gradients (hot spots), even as overall cell temperature increased due to high illuminance levels from light concentration, although specific temperature correlation analysis warrants further study. However, system effectiveness was negligible under tested artificial lighting conditions, highlighting a dependency on natural sunlight characteristics. These findings underscore potential for utilizing simple, cost-effective optical components to substantially optimize solar energy harvesting, particularly for applications in environments with consistent sunlight exposure, thereby advancing sustainable renewable energy solutions.